2015
DOI: 10.1108/imr-03-2014-0089
|View full text |Cite
|
Sign up to set email alerts
|

The impact of CSR on consumer-corporate connection and brand loyalty

Abstract: This paper examined whether companies' health Corporate Social Responsibility (CSR) activities-CSR activities concerning health and well-being of mothers and children-had impacts on perceived quality of life, consumers' brand attitude, and customers' loyalty, with subjective well-being served as moderating variable. The research used both exploratory and conclusive research. Surveys were conducted in two cities in Indonesia, Makassar and Surabaya. Respondents of this research were from two different groups. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 55 publications
0
45
0
Order By: Relevance
“…Brown and Dacin () observed that corporate competence is a function of the expertise of employees, the superiority of internal research and development and the resulting technological innovation, manufacturing expertise, customer orientation and industry leadership (Moon et al, , p. 524). Evidence suggests that when consumers perceive a company's corporate competence positively they will form positive attitudes toward the company and its products.…”
Section: The Research Model and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations
“…Brown and Dacin () observed that corporate competence is a function of the expertise of employees, the superiority of internal research and development and the resulting technological innovation, manufacturing expertise, customer orientation and industry leadership (Moon et al, , p. 524). Evidence suggests that when consumers perceive a company's corporate competence positively they will form positive attitudes toward the company and its products.…”
Section: The Research Model and Hypothesesmentioning
confidence: 99%
“…The self-brand connection was defined as the extent to which consumers reflect their ego concepts in a brand (Choi & Park, 2011;Moon et al, 2015 ;Swaminathan et al, 2007). The self-brand connection was measured by seven items after modifying question items that were used in the existing literature (Moon et al, 2015;Swaminathan et al, 2007).…”
Section: Operational Definition Of Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…In many sources of information authors are concerned about the impact of CRS on brand and customer relationships (Liu, Wong, Shi, Chu, Brock, 2014;Kuo-Fang, Yan, Kuang-Wei, 2014;Khojastehpour, Johns, 2014;Moon, Lee, Oh, 2015;Fatma, Rahman, Khan, 2015;Wolf, Issa, Thiel, 2014;Pogorzelski, 2015;Wang, Korschun, 2015). However, studies on the impact on brand image have not been met.…”
Section: Introductionmentioning
confidence: 99%